Efavirenz Is Predicted To Accumulate in Brain Tissue: an In Silico, In Vitro, and In Vivo Investigation (Antimicrobial Agents and Chemotherapy, 2016)
Adequate concentrations of efavirenz in the central nervous system (CNS) are necessary to suppress viral replication, but high concentrations may increase the likelihood of CNS adverse drug reactions. The aim of this investigation was to evaluate the efavirenz distribution in the cerebrospinal fluid (CSF) and the brain by using a physiologically based pharmacokinetic (PBPK) simulation for comparison with rodent and human data. The efavirenz CNS distribution was calculated using a permeability-limited model on a virtual cohort of 100 patients receiving efavirenz (600 mg once daily). Simulation data were then compared with human data from the literature and with rodent data. Wistar rats were administered efavirenz (10 mg kg of body weight-1) once daily over 5 weeks. Plasma and brain tissue were collected for analysis via liquid chromatography-tandem mass spectrometry (LC-MS/MS). The median maximum concentrations of drug (Cmax) were predicted to be 3,184 ng ml-1 (interquartile range [IQR], 2,219 to 4,851 ng ml-1), 49.9 ng ml-1 (IQR, 36.6 to 69.7 ng ml-1), and 50,343 ng ml-1 (IQR, 38,351 to 65,799 ng ml-1) in plasma, CSF, and brain tissue, respectively, giving a tissue-to-plasma ratio of 15.8. Following 5 weeks of oral dosing of efavirenz (10 mg kg-1), the median plasma and brain tissue concentrations in rats were 69.7 ng ml-1 (IQR, 44.9 to 130.6 ng ml-1) and 702.9 ng ml-1 (IQR, 475.5 to 1,018.0 ng ml-1), respectively, and the median tissue-to-plasma ratio was 9.5 (IQR, 7.0 to 10.9). Although it is useful, measurement of CSF concentrations may give an underestimation of the penetration of antiretrovirals into the brain. The limitations associated with obtaining tissue biopsy specimens and paired plasma and CSF samples from patients make PBPK modeling an attractive tool for probing drug distribution.
This is the accepted author manuscript (AAM). The final published (version of record) is available online via American Society for Microbiology at http://dx.doi.org/10.1128/AAC.01841-16 - please refer to any applicable terms of use of the publisher.
Keywords: RS Pharmacy and materia medica; efavirenz; PBPK; CNS; toxicity